KEPASTIAN HUKUM TERHADAP PERLINDUNGAN PEKERJA OUTSOURCING PASCA UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Tri Widya Kurniasari (Jurnal Geuthèë: Penelitian Multidisiplin, 2022)
submission of work from a company to another party which has the aim of reducing the company's burden. Since the enactment of Law Number 11 of 2020 concerning Job Creation, several subjects in Law Number 13 of 2003 concerning Manpower have undergone changes. The position of the laborer is very weak compared to the position of the owner of the job in practice. Sometimes, these rights are not fulfilled by employers and outsourcing companies. This type of research is a qualitative research, which is used as a research procedure that produces descriptive data on issues related to legal protection for outsourced workers. The research approach used is a combination of normative legal research approaches and legal anthropological approaches. A normative legal research approach is carried out to find out how far the interests and rights of outsourced workers are. Legal protection of outsourcing workers in terms of the principle of legal certainty in Law Number 13 of 2003 concerning Manpower can be seen in two forms, namely legal certainty in preventive protection and legal certainty in repressive protection. Legal certainty in preventive protection includes the certainty of employment relations, namely regarding the status of the employment relationship between outsourced workers and outsourcing companies and the application of the employer. Then the certainty of the type of work of the outsourcing worker, and the certainty of the legal entity form of the outsourcing company. Law Number 11 of 2020 concerning Job Creation changes the term outsourcing from handing over part of the implementation of work to other companies to outsourcing. There is no longer a limit to the types of work that can be outsourced. The Job Creation Law changes the provisions on outsourcing by removing Article 64 and Article 65 and amending Article 66 of the Manpower Act..